PROFESIONALISME, INDEPENDENSI, DAN KUALITAS AUDIT DIMODERASI OLEH TIME BUDGET PRESSURE - Iqbal Najmudin Sholeh; Widyastuti, Shinta (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2025)
This research aims to see whether there is an effect of professionalism and auditor independence on audit quality with time budget pressure as a moderating variable. This study uses a quantitative method with the sample being auditors who are in public accounting firms located in the south Jakarta area. The data collection technique used simple random sampling with a sample size of 110 respondents. The data was processed and tested using the Partial Least Square method with the SmartPLS.3.0 application. The results of this study indicate that auditor professionalism and auditor independence have a significant positive effect on audit. Meanwhile, time budget pressure cannot weakening the relationship between auditor professionalism and auditor independence on audit quality.